Peran Work Discipline, Reward, dan Job Training terhadap Work Achievement pada Karyawan Perumda BPR Bank Daerah Lamongan - Nisa, Khoirotun; Hadi, Hafid Kholidi (Jurnal Ilmu Manajemen, 2021)
Research on work achievement is still relevant and exciting to study in companies worldwide. There are three variables tested for work achievement effects, namely work discipline, rewards, and job training. The location chosen in this study is Perumda BPR Lamongan. This study's population was 130 employees of Perumda BPR Lamongan Regional Bank with 98 samples using a probability sampling method. The data analysis of this study used SPSS, namely multiple linear regression. The results showed that work discipline, rewards, and job training had a significant positive effect on BPR Perumda BPR Lamongan Regency's work achievement, where the Job Training variable had the most significant influence on work achievement.